Sensorimotor polyneuropathy as an initial clinical manifestation of sarcoidosis - Brola, Waldemar; Pejas-Dulewicz, Renata; Wasiński, Jarosław; Paszkiewicz, Jolanta; Fudala, Małgorzata (Medical Studies/Studia Medyczne, 2014)
Sarcoidosis is a multi-organ granulomatous disease of unknown aetiology, most frequently affecting the respiratory system. It usually involves lungs and hilar lymph nodes. Pulmonary symptoms can also be accompanied by lesions located in other organs. Although the nervous system is rarely affected, the neurological symptoms can precede the diagnosis of neurosarcoidosis by several years. In this report we present a case of a 24-year-old male, who reported to his general practitioner due to numbness and hypoaesthesia of distal regions of his upper and lower limbs. Electrophysiological study revealed symmetrical sensorimotor polyneuropathy. Despite the lack of any other symptoms, supplementing the diagnostic evaluation with lung imaging and histopathological examination of bronchial mucous membrane led to the diagnosis of neurosarcoidosis.